Monitoring Leachate Migration in Compacted Soil Using Digital Image Technique - Yamusa, Y. B.; Sa’ari, R.; Ahmad, K.; Alias, N.; Mustaffar, M.; Foong, L. K. (Engineering, Technology & Applied Science Research, 2019)
As leachate has been a source of groundwater contamination worldwide, this paper examines the phenomenon of leachate migration on different gradations of compacted laterite soil used as sanitary landfill liners. Three different soil gradations (30%, 40% and 50% with respect to fines content) used in this study were compacted in circular acrylic columns to provide a clear visualization of leachate migration into the soils. Digital image technique was used in capturing photos at successive time intervals to monitor the leachate migration. The captured digital images were fed into Matlab and converted into hue-saturation-intensity (HSI) format. Surfer software then read the HSI and generated 2D contour plots. The results of the experiments showed that the leachate moves downward faster in the soil gradation with the least fines content. Hydraulic conductivity values decrease with increase in time duration and equally with increase in fines content. The hydraulic conductivities of the leachate for 30%, 40% and 50% fines were 3.64×10-9m/s, 2.40×10-9m/s, and 1.24×10-9m/s respectively. This reveals that for tropical laterite soils, gradation containing 50% fines content provides better hydraulic conductivity. The use of noninvasive digital image technique can enable designers/engineers to monitor and visualize the leachate migration in compacted soils in waste containment application systems.